Girolamo Rainaldi for the Duomo of Milan: the Façade Project of 1642 and some Clarifications on the Graphic Corpus of the Architect - Antonio Russo (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2022)
Our knowledge about the activity of Girolamo Rainaldi (1570-1655) in northernItaly, and particularly inMilan, has recently been enriched with data coming from previously unpublished documents. From those, we discover that the architect was active in theLombardcity for the long-running question of the conclusion of Duomo’s façade, for which a project dating to circa 1607 is preserved in the Ambrosiana Library.